ANALISIS KEPUASAN KERJA KARYAWAN CV. MITRA BELAWAN FISHING MEDAN - WILLIAM VINCENT; HARTONO .; WENY .; YULIANA .; NGAJUDIN NUGROHO (LP2MTBM MAKARIOZ, 2019)
Job satisfaction is defined as a pleasant or unpleasant emotional state in which employees view their work. Job satisfactionreflects one's feelings about their work. This is seen in the positive attitude of employees towards work and everything that isencountered in the work environment. Employee job satisfaction must be created as well as possible so that employeemorale, dedication, love and discipline increase. The informants studied were employees at CV. Mitra Belawan FishingMedan. The research method used is a qualitative method where the data obtained is based on interviews with data sourcesused are primary data. The formulation of the problem in this study,